Sustainable ecological and economic development of mountainous areas through the prism of tariff regulation of nature management - Pityulych Mykhaylo; Пітулич Михайло; Popyk Mariana; Попік Маріана; Kish Galyna; Кіш Галина; Chakiy Olga; Чакій Ольга; Robert Bacho; Роберт Бачо; Bacsó Róbert (EDP Sciences, 2021)
Abstract. The article is focused on the formation of an effective tariff policy for the use of natural resources and environmental pollution. The article substantiates that such a policy should be aimed at minimizing the negative impact of economic and business activities on the environment, which will ultimately increase the efficiency and rational use of available natural resources of separate mountain areas based on their development priorities. The main factors are outlined that stipulate for the complexity and urgency of solving environmental problems in mountain areas, where special attention is focused on the impact of existing economic entities on the use of local natural resources and the impact of their activities on the environment is determined. The article defines the methodological tools for calculating the assessment of the impact of investment projects on the environmental situation of a particular area where the investment project will be implemented. The study reveals methods for calculating two indicators related to emissions of harmful substances into the environment, in particular the calculation of the coefficients of ecological purity of productions for atmosphere and water in some separate areas.
https://www.e3s-conferences.org/articles/e3sconf/abs/2021/31/contents/contents.html
Keywords: economic development; mountainous area; environmental emergency; environmental disaster